SOCIAL SCIENCES AND NATIONAL SECURITY - Stojadinović, Miša; Milošević , Zoran (The Policy of National Security, 2024)
The contribution of social sciences and humanities to the security of people, society and the state is a little studied topic. It goes without saying that every member of society, especially scientists, should contribute to security, primarily through the adoption of an adequate security culture, knowledge and will (to defend the state) that they possess, which presupposes their knowledge of the legal frameworks that regulate this field. The problem of the contribution of social sciences and humanities to national security arose due to uncritical reforms of these fields initiated by Western power centres. The evaluation of scientific works and the actions of scientists is extremely important for the state and requires an organized system, otherwise it can be a significant source of endangering national security. In this paper, the authors analyse the importance attached to social sciences and humanities as well as their evaluation in society. Special importance is given to their study from the aspect of national security. The basic assumption that guides the authors is that insufficient control of science by the state contributes to endangering national security. This does not mean censorship and absolute control at the same time, but the creation of an orderly system within which the authors will be able to strengthen the national and democratic capacities of the state through their work, and not be abused for the sake of its destabilization, which is especially important in crisis areas. At the same time, the problem of insufficient evaluation of the importance of social sciences and humanities in relation to other sciences is highlighted. There is also a crisis of reviewing scientific papers which is resulted by the introduction of ideological criteria for the publication of articles. Thus, when the reviewer determines that the author is from Russia or Serbia, the next question is whether the author considers Crimea to be Russian or Ukrainian, or, whether Kosmet is an independent state or part of Serbia. The attitude of the reviewer depends on the answer. In order to advance in their professions, they need to be published in journals of high categories, most of which are in the West. This again leads to the resolution and declaration of sensitive issues, where papers are immediately disqualified if they do not agree with an accepted ideological matrix. The authors use the method of content analysis and the comparative method in their paper.
Keywords: Science; social and humanistic sciences; national security; education